Hospital nurses and home care providers' experiences of participation in nutritional care among older persons and their family caregivers: a qualitative study. Issue 2 (26th December 2019) - Hestevik, C. H.; Molin, M.; Debesay, J.; Bergland, A.; Bye, A.
Abstract: Background: A person‐centred approach to nutritional care has the potential to increase an older person's role in making informed decisions about their own care and possibly improving their quality of life. However, despite the considerable interest shown in person‐centred nutritional care in recent years, delivery of such care still appears to lack consideration for older persons' needs and preferences. The present study aimed to explore healthcare professionals' views on how older persons and their family caregivers participate in decisions about their own nutritional care and possible barriers for that participation. Methods: Semi‐structured in‐depth interviews with 23 healthcare professionals in acute geriatric care and home care were conducted. Data were analysed thematically. Results: The analysis of the interviews resulted in three main themes: (i) lack of shared decision‐making in nutritional care; (ii) conflict between patient's preferences and standard nutritional care procedures; and (iii) the value of family caregivers who are seldom involved in nutritional care. Conclusions: Healthcare professionals were aware of the importance of actively engaging older persons and their family members in the nutritional care to achieve positive outcomes. However, they encountered individual and structural barriers, including resistance from patients and family caregivers, conflicts between the patients' nutritional wishes and standard nutritional procedures, a wish to shield the family caregivers from the stress of caring for a sick relative, and lack of time and caring structures that facilitate the older persons and their family's active participation.